Selective oxidation of benzyl alcohol through eco-friendly processes using mesoporous V-MCM-41, Fe-MCM-41 and Co-MCM-41 materials - Cánepa, Analía Laura (2017)
MCM-41 nanostructured materials modified with Vanadium, Iron and Cobalt were synthesized by a hydrothermal method. The catalysts were characterized by XRD, UV–Vis-DR, ICP-OES and N2 adsorption. All the catalysts showed good structural order and high specific areas; however the lowest value in these parameters, corresponding to the Co-M(60) sample, could be due to the higher presence of oxide species determined by UV–Vis-DR. These mesoporous metalosilicates were evaluated in the liquid phase oxidation of benzyl alcohol (BzOH) to benzaldehyde (BzH) using H2O2 as oxidant. Results showed that V-M(60) had better catalytic performance than Fe-M(60) and Co-M(60) exhibiting high TON (1100 mol/mol V), selectivity to BzH (95%) and 31.7% yield at 7 h under optimized reaction conditions. The main reason for the enhanced catalytic performance was attributed to the well dispersion of vanadium species in the framework which could be considered as the active sites for the benzyl alcohol oxidation reaction. At the same time, the catalyst could be recovered and effectively reused during three cycles without a significant loss in its activity and selectivity.